CREATIVE TASKS IN ENGLISH LESSONS TO DEVELOP SPEAKING, READING, LISTENING AND WRITING SKILLS.: CREATIVE TASKS IN ENGLISH LESSONS TO DEVELOP SPEAKING, READING, LISTENING AND WRITING SKILLS. - Ukshebaeva, Firuza (Журнал иностранных языков и лингвистики, 2025)
Learning English as a second or foreign language requires the development of four core skills: Speaking, Reading, Listening, and Writing. Traditional methods often focus on repetitive exercises, which may not fully engage students or foster fluency. Creative tasks, such as role-plays, storytelling, and interactive projects, offer dynamic ways to improve these skills while maintaining student motivation. This article examines how such tasks can be implemented effectively in English lessons, drawing on educational theories and practical classroom experiences.